Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Sektor Consumer Non-Cyclicals - Syifatavia Azzahra; Emir Kharismar (Media Bisnis, 2026)
This study was conducted to determine the effect of firm value as an independent variabel on consumer non-cyclicals sector companies. The dependent variables used in this study are profitability, liquidity, leverage, dividend policy, firm size, firm growth. The population used in this study are consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample used in this study consisted of 16 companies totaling 80 data using purposive sampling method. In addition, this study uses multiple regression analysis. The result of this study indicate that profitability and firm size variables affect firm value. While other variables such as liquidity, leverage, dividend policy, firm growth have no effect on firm value. These findings provide important implications for both theory and practice. Theoretically, this study contributes to the development of corporate finance literature by emphasizing that not all financial indicators have a significant role in determining firm value, particularly in the consumer non-cyclicals sector. Practically, investors are encouraged to prioritize profitability and firm size when evaluating investment decisions, while companies should focus on improving operational efficiency and maintaining optimal asset growth to enhance firm value. Additionally, regulators and stakeholders are expected to consider sector-specific characteristics in formulating policies and evaluation frameworks to ensure more accurate assessment of firm performance and sustainability.